Arginase-1 Is Responsible for IL-13-Mediated Susceptibility to Trypanosoma cruzi Infection - Abad Dar, Mahin; Hölscher, Christoph (Frontiers in Immunology, 2018)
Arginase-1 (Arg-1) is a marker for alternatively activated macrophages (aaM) and is mainly induced by the type 2 cytokines interleukin (IL)-4 and IL-13 through the common IL-4 receptor-alpha (R) subunit. Both, Arg-1 and aaM undermine macrophage effector functions against intracellular parasites and are therefore implicated in the susceptibility to infection with Trypanosoma cruzi, the causative agent of Chagas’ disease. However, the involvement of Arg-1 in promoting intracellular replication of T. cruzi in aaM has not been proven so far in vivo. Because Arg-1 is only moderately expressed in T. cruzi-infected wildtype mice, we elucidated the role of Arg-1 and aaM during infection in IL-13-overexpressing (IL-13tg) mice, which are characterized by an inflammation-induced development of aaM and an accompanied elevated expression of Arg-1. In comparison to wildtype littermates IL-13tg mice were highly susceptible to T. cruzi infection with enhanced parasitemia and impaired survival. Importantly, T. cruzi-infected IL-13tg mice developed an elevated alternative macrophage activation with increased arginase activity. To proof the hypothesis, that Arg-1 accounts for the increased susceptibility of IL-13tg mice, we blocked arginase activity in infected IL-13tg mice. Because this arginase inhibition resulted in a decreased susceptibility to experimental Chagas disease our study supports in summary the conclusion that IL-13/IL-4R-driven Arg-1 expression contributes to the permissiveness of the host to T. cruzi infection.